Time Course of Information Processing in Visual and Haptic Object Classification - Martinovic, Jasna; Lawson, Rebecca; Craddock, Matt (Frontiers in Human Neuroscience, 2012)
Vision identifies objects rapidly and efficiently. In contrast, object recognition by touch is much slower. Furthermore, haptics usually serially accumulates information from different parts of objects, whereas vision typically processes object information in parallel. Is haptic object identification slower simply due to sequential information acquisition and the resulting memory load or due to more fundamental processing differences between the senses? To compare the time course of visual and haptic object recognition, we slowed visual processing using a novel, restricted viewing technique. In an electroencephalographic (EEG) experiment, participants discriminated familiar, nameable from unfamiliar, unnameable objects both visually and haptically. Analyses focused on the evoked and induced fronto-central theta-band (5-7 Hz; a marker of working memory) and the occipital upper alpha-band (10-12 Hz; a marker of perceptual processing) locked to the onset of classification. Long-latency modulations of both theta-band and alpha-band activities differentiated between familiar and unfamiliar objects in haptics. Decreases in right occipital alpha-band activity for haptic identification of unfamiliar relative to familiar objects indicate a likely processing role of multisensory extrastriate areas. In contrast, differential visual processing of familiar and unfamiliar objects was characterized only by a relatively early difference in left occipital upper alpha-band activity. We conclude that haptic object recognition relies on common representations with vision but also that there are fundamental differences between the senses that do not merely arise from differences in their speed of processing.